Join the growing community of curious minds on IDNLearn.com and get the answers you need. Join our Q&A platform to get accurate and thorough answers to all your pressing questions.
Sagot :
Substitute -x-2 for y in 3x+3y=6
3x+3y=6
3x+3(-x-2)=6
-6=6 (Simplify both sides of the equation)
-6+6=6+6 ( add six to both sides)
0=12
Answer: No Solutions
Hope this helped
3x+3y=6
3x+3(-x-2)=6
-6=6 (Simplify both sides of the equation)
-6+6=6+6 ( add six to both sides)
0=12
Answer: No Solutions
Hope this helped
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. Your search for solutions ends here at IDNLearn.com. Thank you for visiting, and come back soon for more helpful information.